Emission Of Selected Environmental Exposure From Selective Laser Sintering (SLS) Polyamide Nylon (PA12) 3D Printing Process - Muhamad Damanhuri, Amir Abdullah; Omar, Mohammad Rafi; Hariri, Azian; Md Fauadi, Muhammad Hafidz Fazli; Alkahari, Mohd Rizal (FAZ Publishing, 2019)
Indoor Air Quality (IAQ) is very important to the health and comfort of occupants inside building. The quality of indoor air depends on the air pollutant inside the building. A bad IAQ in workplace will lead to negative impacts to the operators such as dizziness, irritation, headache and others. Additive manufacturing is one of the emerging technologies that has been discussed recently. However, the study on emission from 3D printing process are still focusedon FDM type 3D printer. Less attention given to the other type of 3D printing especially powder bed fusion particularly selective laser sintering (SLS). Therefore, this study aims to investigates the emission from selective laser sintering of 3D printing process. The design calibration block from SLS printer’s manufacturer is selected to be printed to measure the emission from SLS printing. The powder material use in this research was polyamide nylon (PA12) powder material. The data collected for 8 hours during whole printing process. Temperature, relative humidity, carbon dioxide (CO2), total volatile organic compound (TVOC), and formaldehyde were measured and compared to the acceptable limit for Industrial Code of Practice (ICOP) DOSH 2010. The highest concentration of carbon dioxide CO2 is at preparation for during printing phase 999 ppm and almost exceed the limit of 1000 ppm. Meanwhile, TVOC, formaldehyde, RH and temperature were measured at 1.7 ppm, 0.05 ppm, 70.6%, and 27.6 °C accordingly. The concentration of TVOC and formaldehyde are in the range of acceptable limit. RH and temperature meanwhile slightly over acceptable limit during SLS machine operation due to laser temperature. The data collected from the emissions of selective laser sintering (SLS) 3D printing by polyamide nylon powder suggest that ventilation system of the location should be improved to remove excess pollutant air and fresh air is suggest to supply constantly to the occupant.